Transformation from Below in Bangladesh: Decentralization, local governance, and systemic change*. (12th January 2018) - FAGUET, JEAN-PAUL
Abstract: I examine decentralization through the lens of the local dynamics it unleashed in Bangladesh. I argue that the national effects of decentralization are largely the sum of its local-level effects. Hence, to understand decentralization, we must first understand how local government works. This implies analysing not only decentralization, but also democracy, from the bottom up. I present a model of local government responsiveness as the product of political openness and substantive competition. The quality of politics, in turn, emerges endogenously as a joint product of the lobbying and political engagement of local firms/interests, and the organizational density and ability of civil society. I then test these ideas using qualitative data from Bangladesh. The evidence shows that civic organizations worked with non-governmental organizations and local governments to effect transformative change from the grass roots upwards—not just to public budgets and outputs, but to the underlying behaviours and ideas that underpin social development. In the aggregate, these effects were powerful. The result, key development indicators show, is Bangladesh leap-frogging past much wealthier India between 1990 and 2015.